2022
DOI: 10.1002/oby.23515
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for obesity and overweight in Chinese children: a nationwide survey

Abstract: Objective: This study aimed to analyze a comprehensive set of potential risk factors for obesity and overweight among Chinese children with a full range of ages and with wide geographical coverage. Methods: In the Prevalence and Risk Factors for Obesity and Diabetes in Youth (PRODY) study (2017-2019), the authors analyzed 193,997 children aged 3 to 18 years from 11 provinces, autonomous regions, and municipalities that are JingNan Chen and Lu Jin contributed equally to this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…However, a national study found that higher consumption of animal offal was associated with a lower risk of obesity [53]. The difference may be because the latter subjects were children.…”
Section: Multilevel Logistic Regression Analysismentioning
confidence: 99%
“…However, a national study found that higher consumption of animal offal was associated with a lower risk of obesity [53]. The difference may be because the latter subjects were children.…”
Section: Multilevel Logistic Regression Analysismentioning
confidence: 99%
“…Healthy diet, increased physical activity, and weight loss should be encouraged for overweight individuals [41]. Of importance, universal education for obesity control must provided to better inform the public in Mainland China [42], in particular, promoting changes in lifestyle and diet for Chinese children to help relieve the future obesity burden [43].…”
Section: Introductionmentioning
confidence: 99%
“…First, they described the distribution characteristics of people who are overweight and obese in the Chinese population and also analyzed the changing trends in the burden of being overweight and obese in the country ( 8 , 9 ). Second, these researchers explored the influencing factors and related mechanisms of obesity through animal experiments and population surveys ( 10 , 11 ). Another important research direction was to explore how to diminish the incidence of obesity and reduce the burden of obesity-related diseases based on the previous two aspects ( 12 ).…”
Section: Introductionmentioning
confidence: 99%